After the Arab Revolutions Decentring Democratic Transition Theory - El-Affendi, Abdelwahab (Edinburgh University Press, 2022)
Incorporates the lessons learned from the 2011 Arab revolutions into democratic transition theoryRadically reclaims and reformulates democratic transition theory, taking the Middle East and not the West as its focal point Argues that recent Arab transitions are central to our understanding of the dynamics of democratisation, even in advanced democraciesFeatures contributions from prominent authors and intellectuals such as Azmi Bishara, Hamid Dabashi and Asef BayatAfter the Arab Revolutions brings together experienced scholars from the region and beyond to cast new light on the challenges facing democratic transitions and democratic stability. Rather than taking refuge in 'context' and 'regional specificity' to excuse failures to unpack Arab politics, the book argues that sound political science should - and could - prove relevant across regions and cultures.This radical critique reclaims and recasts the 'Transition Paradigm', countering the habit of using advanced and successful democratic transitions as a template to be followed in other regions. It argues that the Arab (and broader Middle Eastern) experience has important lessons to offer, even in its failures. For example, it could help to explain the West's recent populist upsurge and other democratic reversals